Kajian Kemampuan Argumentasi Siswa pada Materi Pokok Animalia Melalui Pendekatan Saintifik di SMA dengan Peringkat Akreditasi yang Berbeda - Tantri Dewantari; Neni Hasnunidah; Dina Maulina (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2022)
This study aims to determine the differences in the argumentation ability of students in high school with different accreditation ratings. The method used is a survey with an ex post facto research design and a sample selection technique using purposive sampling. The results of the student's argumentative ability test were analyzed statistically with the ANOVA test with a significance level of 5% and the data from interviews and teacher questionnaires were analyzed descriptively. The results showed that the argumentation ability of students in schools with accreditation ratings A was significantly different from those with accreditation ratings B and C. In addition, the argumentation ability of students in schools with accreditation rating B was significantly different from those with accreditation rating C. In conclusion, the average value of argumentation ability of students in high school with accreditation ratings of A, B and C on the subject matter of Animalia has a significant difference. Keywords: Accreditation, Animalia, Argumentation, Scientific Approach